2023
DOI: 10.1039/d3dt00140g
|View full text |Cite
|
Sign up to set email alerts
|

A novel 2,6-bis(benzoxazolyl)phenol macrocyclic chemosensor with enhanced fluorophore properties by photoinduced intramolecular proton transfer

Abstract: The macrocyclic ligand L, in which a triethylentetramine incorporates a 2,6-bis(2-benzoxazolyl)phenol (bis-HBO) group, was designed and synthesized with the aim to create a chemosensor with high selectivity and specificity for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The emission of ESIPT-capable dyes is highly sensitive to solvents, 43–50 substitution in the ESIPT-dye core, 51–71 protonation/deprotonation, 72–80 and coordination of metal ions. 81–96 Normally, the latter process is coupled with the deprotonation of ESIPT-dyes. 81–96 However, the rational design of ESIPT-capable molecules featuring spatially separated sites for accommodating both a metal ion and the mobile H + ion, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The emission of ESIPT-capable dyes is highly sensitive to solvents, 43–50 substitution in the ESIPT-dye core, 51–71 protonation/deprotonation, 72–80 and coordination of metal ions. 81–96 Normally, the latter process is coupled with the deprotonation of ESIPT-dyes. 81–96 However, the rational design of ESIPT-capable molecules featuring spatially separated sites for accommodating both a metal ion and the mobile H + ion, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…81–96 Normally, the latter process is coupled with the deprotonation of ESIPT-dyes. 81–96 However, the rational design of ESIPT-capable molecules featuring spatially separated sites for accommodating both a metal ion and the mobile H + ion, i.e. , the metal binding site and the ESIPT site, paves the way toward the coordination of metal ions without the deprotonation of the ESIPT-dyes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%